PEMBUATAN DAN PENGUJIAN PRAKTIKALITAS PERANGKAT PERCOBAAN KONSEP KALORIMETRI GAS SEBAGAI MEDIA PEMBELAJARAN FISIKA SMA - Rika Wulandara; Hendar Sudrajat; Azizahwati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aimed to examine the practicalities of products resulting from the research design and experimental validation of the concept calorimetry gas as a medium of learning high school physics that has been done before. In this study, the experimental concept of gas calorimetry tested for use at 15 students and 3 teachers from AL-FITYAH SMA and SMA 12 Pekanbaru. In this study, the teacher acts as an observer and student acts as a user. Based on the analysis of data on the observation of the practicalities of votes according to observers, showed that the experimental device is practically used as a medium of learning with the criteria of High and Very High. While data on the practicalities assessment questionnaire by the user, it also shows that the experimental device is practically used as a medium of learning with the criteria of High and Very High. Overall, the learning device calorimetry gas concept makes it easy for teachers and students as medium of learning with criteria Very High.Keywords: Crossword Puzzle Method, Cooperative Learning, the Scientific Attitude